2015
DOI: 10.1039/c4ra13281e
|View full text |Cite
|
Sign up to set email alerts
|

Unique self-assembly behavior of amphiphilic block copolymers at liquid/liquid interfaces

Abstract: Various microstructures of amphiphilic block copolymers were fabricated at the liquid/liquid interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…5 We subsequently investigated this system systematically and found that foam, honeycomb, and network structures can be fabricated at the liquid/liquid interface by varying the concentration of HAuCl 4 or by changing the length of blocks. 6 Shortly afterwards we developed a new liquid/liquid interfacial self-assembly method to fabricate microstructures of the block copolymer polystyrene-b-poly(acrylic acid)-b-polystyrene (PS-b-PAA-b-PS) with metal ions. 7 This polymer was first dissolved in DMF/CHCl 3 to form a mixed solution because of the strong polarity of the PAA block.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 We subsequently investigated this system systematically and found that foam, honeycomb, and network structures can be fabricated at the liquid/liquid interface by varying the concentration of HAuCl 4 or by changing the length of blocks. 6 Shortly afterwards we developed a new liquid/liquid interfacial self-assembly method to fabricate microstructures of the block copolymer polystyrene-b-poly(acrylic acid)-b-polystyrene (PS-b-PAA-b-PS) with metal ions. 7 This polymer was first dissolved in DMF/CHCl 3 to form a mixed solution because of the strong polarity of the PAA block.…”
mentioning
confidence: 99%
“…This is in stark contrast to the PS-b-P2VP systems where the polymer chloroform solution instead of the mixed DMF/chloroform solution was used as the organic phase and composite thin films formed at the liquid/liquid interface. 5,6 When PS-b-PAA-b-PS instead of PS-b-P2VP was used, a film formed at the liquid/liquid interface rather than at the air/liquid interface. 7 This was attributed to the different hydrophilic-lipophilic balance properties of these two polymers: PS-b-PAA-b-PS is a good emulsifier capable of stabilizing the W/O emulsion formed in the lower phase, whereas PS-b-P2VP is not.…”
mentioning
confidence: 99%
“…1(e) and (f)). As revealed in our previous work, 27,29 the formed microstructures depended on experimental conditions, including the polymer structure, the inorganic species, and the concentrations. Hence, the PI-b-P2VP/Ag and PI-b-P2VP/Au composite lms exhibited different morphologies.…”
Section: Resultsmentioning
confidence: 52%
“…Generally, this kind of lm should be formed at the liquid/liquid interface in the presence of inorganic or other species in the aqueous phase that strongly interact with the polymer molecules in the organic phase, as described in our previous work [25][26][27][28][29] and other literature. Generally, this kind of lm should be formed at the liquid/liquid interface in the presence of inorganic or other species in the aqueous phase that strongly interact with the polymer molecules in the organic phase, as described in our previous work [25][26][27][28][29] and other literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation